2021
DOI: 10.1136/bmjopen-2020-042510
|View full text |Cite
|
Sign up to set email alerts
|

Music intervention for sleep quality in critically ill and surgical patients: a meta-analysis

Abstract: ObjectiveSleep disruption occurs frequently in hospitalised patients. Given the potential of music intervention as a non-pharmacological measure to improve sleep quality, we aimed to assess and quantify current literature on the effect of recorded music interventions on sleep quality and quantity in the adult critical care and surgical populations.DesignSystematic review and meta-analysis.Data sourcesEmbase, MEDLINE Ovid, Cochrane Central, Web of Science and Google Scholar.Eligibility criteria for studiesRando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 98 publications
2
15
0
Order By: Relevance
“…Moreover, the efficacy of music as a non-pharmacological intervention to enhance sleep in critically ill individuals finds support in recent meta-analysis findings from 202. [52] These results align with our own investigation, Table 3 Efficacy of different comparisons for sleep quality by SMDs and corresponding 95% CrIs.…”
Section: Compared With Previous Meta-analysissupporting
confidence: 87%
“…Moreover, the efficacy of music as a non-pharmacological intervention to enhance sleep in critically ill individuals finds support in recent meta-analysis findings from 202. [52] These results align with our own investigation, Table 3 Efficacy of different comparisons for sleep quality by SMDs and corresponding 95% CrIs.…”
Section: Compared With Previous Meta-analysissupporting
confidence: 87%
“…Music intervention has shown some promise in improving perioperative sleep. A systematic review and meta-analysis demonstrated that administering soothing music to ICU and surgical patients for an average of 40 minutes using headphones or earphones during the day or night before sleep, had a significant effect on subjective sleep quality 106…”
Section: Measurements Of Sleep Disturbancesmentioning
confidence: 99%
“…Figure 1 C illustrates the prospects of creating mutually beneficial interactions when integrating biophilic design and indoor environments supporting disease-specific self-care. The network of diverse physiological responses to such therapeutic interior environments is supported by accumulating studies showing that nature-based interventions and listening to music can improve depressive symptoms and pain (e.g., [ 19 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ] while also improving sleep [ 45 , 46 , 47 , 48 ]. It is noteworthy that all three—nature-based interventions, listening to music and quality sleep—can also positively impact immune functions [ 33 , 49 , 50 ].…”
Section: Integrating Biophilic Design and Self-care To Create Therape...mentioning
confidence: 99%